Synthesis and antiproliferative evaluation of glucosylated pyrazole analogs of K252c. Issue 8 (22nd February 2018) - Douara, Bachir; Esvan, Yannick J.; Pereira, Elisabeth; Giraud, Francis; Volodina, Yulia L.; Kaluzhny, Dmitry N.; Shtil, Alexander A.; Anizon, Fabrice; Moreau, Pascale
Abstract: Pyrazole analogs of the staurosporine aglycon K252c were recently described as potent inhibitors of the three Pim protein kinase isoforms. To evaluate the impact of the introduction of a sugar moiety on the biological activities of this heterocyclic scaffold, four new glucosylated pyrazole analogs of K252c were synthesized. Their biological evaluation demonstrated that most active compounds11 and19 substituted by a β-d -glucosyl moiety at N12 or N13 positions exhibited antiproliferative activities toward HCT116 cells. Graphical abstract: